2021
DOI: 10.3390/ijerph18052446
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Safe on Australian Roads: Overview of Key Determinants of Risky Driving, Passenger Injury, and Fatalities for Indigenous Populations

Abstract: Social and cultural barriers associated with inequitable access to driver licensing and associated road safety education, as well as socioeconomic issues that preclude ongoing vehicle maintenance and registration, result in unsafe in-car behaviours such as passenger overcrowding. This in turn is associated with improper seatbelt usage, noncompliance with child restraint mandates, and driver distraction. For example, in Australia, where seatbelt use is mandatory, Indigenous road users are three times less likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…Epidemiological studies have shown MVC fatality risk for Australian demographic groups is variable when it comes to age, 23,24 sex, 25 and Aboriginal and Torres Strait Islander status. 26 Contrary to standardised mortality ratios derived from 1997 to 1996 data, our results indicate that females in rural areas are at a significantly higher risk of fatal crashes in comparison with their metropolitan counterparts than males. 25 The influence of duration and frequency of road travel on the differences in relative risk between gender groups is unknown and cannot be determined by our data.…”
Section: Demographicscontrasting
confidence: 99%
“…Epidemiological studies have shown MVC fatality risk for Australian demographic groups is variable when it comes to age, 23,24 sex, 25 and Aboriginal and Torres Strait Islander status. 26 Contrary to standardised mortality ratios derived from 1997 to 1996 data, our results indicate that females in rural areas are at a significantly higher risk of fatal crashes in comparison with their metropolitan counterparts than males. 25 The influence of duration and frequency of road travel on the differences in relative risk between gender groups is unknown and cannot be determined by our data.…”
Section: Demographicscontrasting
confidence: 99%
“…These trends are evident outside of the UK. According to [3], almost half of the reported driving offences in the Northern Territory of Australia are regulatory; these include speeding and non-adherence to road rules. In Norway, a longitudinal study conducted on 145 young drivers (up to 25 years old) found that speeding behaviour was the main factor (80%) in causing motor vehicle collisions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that delves into the determinants of road fatalities do not account for spatial interactions (Ali et al, 2019;Dhibi, 2019;Saeednejad, et al, 2020;Pammer, et al 2021;Prada, 2021). Erdogan (2009) used Geographic Weighted Regression (GWR) to investigate road mortality across Turkish provinces in 2003, examining death rates alongside vehicle counts separated by their type, such as cars and buses.…”
Section: Literature Reviewmentioning
confidence: 99%